Penerapan Metode Giving Question and Getting Answer untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - Yulianti, Hesti; Iwan, Cecep Darul; Millah, Saeful (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This class action research aims to improve the quality of student learning outcomes in Islamic Religious Education subjects. The alternative offered to achieve that goal is to introduce the giving question and getting answer method. This study uses the Classroom Action Research (CAR) method of Kurt Lewin's model. Data collection techniques used were observation and tests. Classroom Action Research in class VIII H, SMP Negeri 1 Baregbeg, Ciamis Regency. The steps of data analysis are as follows: data selection, data correction and data weighting. The results of this study prove that the giving question and getting answer method has succeeded in improving the quality of student learning outcomes in Islamic Religious Education subjects at the Baregbeg State Middle School in Ciamis Regency.